Analisis Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik Atas Persediaan Pada SPBU 14202146 - Henny Andriyani Wirananda; Alistraja Dison Silalahi (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study is to analyze the application of accounting standards to entities that do not have public accounting obligations for SPBU 14202146 shares. This study uses a qualitative descriptive approach to find out whether the company's accounting standards are working well or not and to find out whether the accounting standards are working well or not. the inventory complies with the regulations of the company. The subject of this investigation is SPBU 14202146 and the subject of this investigation is stock reports and financial statements such as profit and loss and balance sheet of gas station SPBU 14202146 36 months. The analysis technique used is qualitative. The results showed that SPBU 14202146 did not properly implement accounting standards for entities that do not have public responsibility. This is due to the fact that SPBU 14202146 presents the income statement only as a financial statement. Based on the results of the analysis, it is also known that SPBU 14202146 did not apply entity financial accounting standards without public accountability (Entity Financial Accounting Standards Without Public Accountability) in the oil delivery report. Keywords: SAK ETAP, Inventory, Accountability